Notice of meeting - Archives of the Trades Union Congress; Morgan, Betty
038-0093-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 16th June, 1939 There will be a meeting of the Basque Children's Administrative Sub-Committee on MONDAY, JUNE 19th, 1939 at 5.0 p.m. at the above address. It is very much hoped that you will be able to attend. BETTY MORGAN. Organising Secretary. 292/946/38/93